It's 'B Sharp' - Unknown (Daily Express)
This picture depicts Len "Boogsie" Sharpe, one of the leading pannists in action during the Pan Shoot-out.
Keywords: Arrangers (Musicians) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Music -- Performance; Steel bands (Music) -- Trinidad and Tobago